Analysis of the Police's Efforts and Related Agencies in Conducting Development and Improving Performance in Disclosing Criminal Acts in Corruption Cases - Mario Michael Tambunan; Basir S.; Sylvia Prisca Delima (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
Corruption remains a critical issue undermining governance, public trust, and development, particularly in developing countries. The Indonesian National Police (Polri), alongside institutions such as the Corruption Eradication Commission (KPK) and the Attorney General's Office, plays a pivotal role in addressing this challenge. This study examines the efforts and strategies implemented by the police and related agencies in enhancing their performance in the investigation and disclosure of corruption crimes. This research employs a qualitative method through a case study approach, focusing on institutional coordination, capacity building, legal framework improvements, and inter-agency collaboration. The findings indicate that while progress has been made in strengthening investigative capacity through training, organizational reform, and technological advancement, significant obstacles persist. These include bureaucratic inefficiencies, limited human resources, lack of political will, and legal loopholes exploited by corrupt actors. Moreover, the study highlights the importance of synergizing institutional roles to avoid overlapping duties and to enhance the overall effectiveness of anti-corruption efforts. It also emphasizes the need for continuous evaluation and development programs aimed at boosting the professionalism and integrity of law enforcement officers. In conclusion, a multi-sectoral and sustainable approach involving both preventive and repressive strategies is essential to improve performance in combating corruption. The study recommends stronger institutional integration, enhanced resource allocation, and the establishment of a clear performance evaluation system to ensure measurable progress in corruption case disclosure.